Selective internal radiation therapy of metastatic breast cancer to the liver: A meta-analysis - Liu, Chenyu; Tadros, George; Smith, Quinn; Martinez, Linda; Jeffries, James; Yu, Zhiyong; Yu, Qian (Frontiers in Oncology, 2022)
Introduction: To conduct a meta-analysis to assess the efficacy of yttrium-90 selective internal radiation therapy (SIRT) in treating breast cancer patients with hepatic metastasis Method: PubMed and The Cochrane Library Database were queried from establishment to January 2021. The following keywords were implemented: “breast”, “yttrium”, and ”radioembolization”. The following variables and outcomes were collected: publication year, region, sample size, study design, presence of extrahepatic disease, tumor burden, infused radioactivity, breast cancer subtype, previous treatment, median survival time (MST), length of follow-up, adverse events, and radiographical response such as Response Evaluation Criteria in Solid Tumors (RECIST), modified RECIST (mRECIST), and Positron Emission Tomography Response Criteria in Solid Tumors. RESULTS: A total of 24 studies from 14 institutions were included in the present meta-analysis. Based on data of 412 patients, post-embolization MST was 9.8 (95%CI: 9.0-11.6) months. Patients with additional extrahepatic metastasis had a poorer survival rate compared to those with localized hepatic metastasis-only (MST: 5.3 vs 15 months, p<0.0001). Patients with <25% liver tumor burden exhibited more promising survival than those with>25% (MST: 10.5 vs 6.8 months, p<0.0139). Based on RECIST, mRECIST, and PERCIST criteria, TRR was 36% (95%CI: 26-47%), 49% (95%CI: 34-65%), and 47% (95%CI:17-78%), respectively, whereas TCR was 85% (95%CI:76-93%), 73% (95%CI:59-85%), and 97% (95%CI:91-100%), respectively. Conclusion: Based on available published evidence, SIRT is feasible and effective in treating breast cancer with liver metastasis. Patients with lower hepatic tumor burden and without extrahepatic metastasis demonstrated more survival benefit. Future randomized controlled trials are warranted.